1998
DOI: 10.1111/j.1439-0442.1998.tb00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Histamine Concentration in Chicken Oviduct During the Egg‐Laying Cycle

Abstract: Tlus study was undertaken to determine histamine concentration in chicken oviductal parts (infundibulum, magnum, isthmus and shell gland) in relation to the egg location within the oviduct and ovulation.The experiment was performed on Hisex Brown laying hens with regular sequences of at least four eggs.Ovulation occurred within 5-15 min of oviposition of the previous egg in the series. Histamine was determined spectrofluorometrically in the following stages of the egg-laying cycle: during c2 oviposition; 0.5 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Treatment of laying hens with TMX caused a significant decrease in egg laying rate. This result is consistent with previous findings which had shown that treatment of laying hens with TMX leads to a gradual decrease in egg laying rate, evokes pause in egg laying and provokes moulting (Stake et al., 1979; Paczoska‐Eliasiewicz et al., 1998; Sechman et al., 1999). The observed decrease in the egg laying rate observed after TMX treatment might be associated with the inhibition of estradiol priming effect on the hypothalamo‐hypophyseal axis and attenuation of the axis response to progesterone, the hormone responsible for triggering the pre‐ovulatory LH surge (Wilson and Sharp, 1975; Wilson and Cunningham, 1981; Kawashima et al., 1982).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Treatment of laying hens with TMX caused a significant decrease in egg laying rate. This result is consistent with previous findings which had shown that treatment of laying hens with TMX leads to a gradual decrease in egg laying rate, evokes pause in egg laying and provokes moulting (Stake et al., 1979; Paczoska‐Eliasiewicz et al., 1998; Sechman et al., 1999). The observed decrease in the egg laying rate observed after TMX treatment might be associated with the inhibition of estradiol priming effect on the hypothalamo‐hypophyseal axis and attenuation of the axis response to progesterone, the hormone responsible for triggering the pre‐ovulatory LH surge (Wilson and Sharp, 1975; Wilson and Cunningham, 1981; Kawashima et al., 1982).…”
Section: Discussionsupporting
confidence: 93%
“…The observed increase might be the result of the gradual adaptation of the immunological system to the anti‐estrogen factor. Moreover, it seems likely that the increase in plasma Ig can be associated with atresia of yellow hierarchical follicles that was observed following TMX treatment (Stake et al., 1979; Paczoska‐Eliasiewicz et al., 1998). It was found that atresia, and subsequent regression and resorption of ovarian follicles is associated with intensive transport of yolk constituents, including immunoglobulins, from the ovarian follicles back to blood circulation (Shippee et al., 1980; Griffin et al., 1984; Johnson, 2000).…”
Section: Discussionmentioning
confidence: 99%